Association between Hypodontia and Angle’s Malocclusions among Orthodontic Patients in Kathmandu, Nepal - Sanjay Prasad Gupta; Samarika Dahal; Khushboo Goel; Amar Bhochhibhoya; Shristi Rauniyar (International Journal of Dentistry)
Background. Disturbances during the early tooth development stages may result in the congenital absence of teeth. The purpose of this study was to assess the relationship between hypodontia and Angle’s malocclusions. Materials and Methods. The sample comprised 601 orthodontic patients’ pretreatment records (242 men and 259 women), selected from the achieved orthodontic records. Developmental anomalies of teeth affecting the number were examined on dental panoramic radiographs. Based on Angle’s classification, pretreatment dental casts were assessed and classified into different classes of malocclusion. The relationship between hypodontia and different classes of malocclusion was evaluated using the chi-square test. Results. The prevalence of tooth agenesis was 7.48%, that is, 45 out of 601 samples. There were a total of 72 (0.42%) missing teeth, excluding the third molars. The most frequent missing tooth was the maxillary lateral incisor (35, 48.61%), followed by the mandibular lateral incisor (14, 19.44%), the mandibular central incisor (6, 8.33%), the mandibular second premolar (5, 6.294%), and the maxillary second premolar (4, 5.55%). Hypodontia was more common in the upper jaw. Although hypodontia was mostly seen in Class I malocclusion patients (7.87%), followed by Class II malocclusion patients (6.99%) and least in Class III malocclusion patients. However, there was no significant difference in hypodontia among different classes of malocclusions (p = 0.352). Conclusion. The most frequently missing tooth was the maxillary lateral incisor, followed by lateral and central mandibular incisors and mandibular second premolars, while excluding the third molars. The present study did not find any association between various types of malocclusions and hypodontia.